Cost-Effectiveness of Adjuvant FOLFOX and 5FU/LV Chemotherapy for Patients with Stage II Colon Cancer. (May 2013) - Ayvaci, Mehmet U. S.; Shi, Jinghua; Alagoz, Oguzhan; Lubner, Sam J.
Purpose . We evaluated the cost-effectiveness of adjuvant chemotherapy using 5-fluorouracil, leucovorin (5FU/LV), and oxaliplatin (FOLFOX) compared with 5FU/LV alone and 5FU/LV compared with observation alone for patients who had resected stage II colon cancer.Methods . We developed 2 Markov models to represent the adjuvant chemotherapy and follow-up periods and a single Markov model to represent the observation group. We used calibration to estimate the transition probabilities among different toxicity levels. The base case considered 60-year-old patients who had undergone an uncomplicated hemicolectomy for stage II colon cancer and were medically fit to receive 6 months of adjuvant chemotherapy. We measured health outcomes in quality-adjusted life-years (QALYs) and estimated costs using 2007 US dollars.Results . In the base case, adjuvant chemotherapy of the FOLFOX regimen had an incremental cost-effectiveness ratio (ICER) of $54, 359/QALY compared with the 5FU/LV regimen, and the 5FU/LV regimen had an ICER of $14, 584/QALY compared with the observation group from the third-party payer perspective. The ICER values were most sensitive to 5-year relapse probability, cost of adjuvant chemotherapy, and the discount rate for the FOLFOX arm, whereas the ICER value of 5FU/LV was most sensitive to the 5-year relapse probability, 5-year survival probability, and the relapse cost. The probabilistic sensitivity analysis indicates that the ICER of 5FU/LV is less than $50, 000/QALY with a probability of 99.62%, and the ICER of FOLFOX as compared with 5FU/LV is less than $50, 000/QALY and $100, 000/QALY with a probability of 44.48% and 97.24%, respectively.Conclusion . Although adjuvant chemotherapy with 5FU/LV is cost-effective at all ages for patients who have undergone an uncomplicated hemicolectomy for stage II colon cancer, FOLFOX is not likely to be cost-effective as compared with 5FU/LV.